Intertemporal changes in the antecedents of migration in 1990-2000 period: the case of Malaysia and Asia-Pacific countries - Chee, Seong Ow; Baharom, Abdul Hamid; Habibullah, Muzafar Shah (Emerald Group Publishing, 2014)
Purpose – The purpose of paper is to investigate and determine the intertemporal changes in linkages between migration (both emigration and immigration) and economic conditions in during 1990-2000 period.